Light Manufacturing in Tanzania: A Reform Agenda for Job Creation and Prosperity - Dinh, HinhT. (World Bank, 2015)
Light Manufacturing in Tanzania argues that for Tanzania to remain one of the fastest growing economies in Sub-Saharan Africa, it has to make progress in the structural transformation that can lift workers from low-productivity agriculture and the informal sector to higher productivity activities. Manufacturing, which has been the main vehicle throughout the world to achieve this transformation, has remained stunted in Tanzania. Using new evidence, the book shows that feasible, low-cost, sharply focused policy initiatives aimed at enhancing private investment could launch Tanzania on a path to competitive light manufacturing. These initiatives would complement progress on broader investment reforms by increasing the share of industry in regional output and raising the market share of domestically produced goods in rapidly growing local markets for light manufactures. And, as local producers increase their scale, improve quality, and gain experience with technology, management, and marketing, they can take advantage of emerging export opportunities. In Tanzania, as in East Asia, policies that encourage foreign direct investment can speed industrial development and the expansion of exports. The impact of isolated successes can be multiplied. The strategies proposed here can launch a process that would create millions of productive jobs. Light Manufacturing in Tanzania has several innovative features. First, it provides in-depth cost comparisons between Tanzania and four other countries in Asia and Africa at the sector and product levels. Second, the book uses a wide array of quantitative and qualitative techniques to identify key constraints to enterprises and to evaluate differences in the performance of firms across countries. Third, it uses a focused approach to identify country- and industry-specific constraints. Fourth, it highlights the interconnectedness of constraints and solutions. For example, solving the manufacturing input problem requires actions in agriculture, education, and infrastructure. Detailed cross-country analysis was carried out in four subsectors in Tanzania: textiles and apparel, leather products, wood products, and agroprocessing. Based on this analysis, the book suggests directing government policies toward removing constraints in a few of the most promising light manufacturing sectors using practical and innovative solutions inspired by the fast-growing Asian economies the starting point of which 20 years ago was not so different from Tanzania's today. This book will be valuable to African policy makers, professional economists, and anyone interested in economic development, industrialization, and the structural transformation of developing countries. Endorsements: "Economic development should be viewed as a process of persistent structural change, which, if successful, supports constant technological upgrading of production and trade. For developing countries, industrialization was never an end in itself, but the principal means at their disposal to obtain a share of the benefits of technological progress and gradually raise the standard of living of their population. It was, and remains, necessary in order to take advantage of its externalities and dynamic economies of scale. This book builds on that theoretical framework and offers a strong policy rationale for labor-intensive industries in Tanzania. It is also a practical blueprint for employment creation in low-income countries.”